2002
DOI: 10.1111/j.1749-6632.2002.tb04277.x
|View full text |Cite
|
Sign up to set email alerts
|

Eicosanoids and the Regulation of Cardiac Glucose Transport

Abstract: Intact actin microfilaments are necessary for insulin‐regulated GLUT4 translocation from intracellular pools to the plasma membrane. Products of the lipoxygenase (LO) pathway were shown to be implicated in the regulation of actin cytoskeleton rearrangement. The aim of this study was to examine the role of these LO products for cardiac insulin signaling and glucose uptake, GLUT4 translocation, and actin‐based cytoskeleton structure. Exposure of cardiomyocytes to esculetin or NDGA, two structurally different LO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…These include the regulation of ion channel kinetics (53-56), contractility (53, 57), metabolic flux, and bioenergetic efficiency (58 -60). For example, lipoxygenase inhibi- tion has been demonstrated to block insulin-mediated glucose uptake in cultured ventricular myocytes suggesting the importance of downstream lipoxygenase metabolites in insulin signaling (61). Furthermore, 12-HETE has been previously demonstrated to increase myocardial mitochondrial Ca 2ϩ content as well as mitochondrial nitric-oxide synthase activity, which led to increased apoptosis in HL-1 cardiac myocytes (51,62).…”
Section: Discussionmentioning
confidence: 99%
“…These include the regulation of ion channel kinetics (53-56), contractility (53, 57), metabolic flux, and bioenergetic efficiency (58 -60). For example, lipoxygenase inhibi- tion has been demonstrated to block insulin-mediated glucose uptake in cultured ventricular myocytes suggesting the importance of downstream lipoxygenase metabolites in insulin signaling (61). Furthermore, 12-HETE has been previously demonstrated to increase myocardial mitochondrial Ca 2ϩ content as well as mitochondrial nitric-oxide synthase activity, which led to increased apoptosis in HL-1 cardiac myocytes (51,62).…”
Section: Discussionmentioning
confidence: 99%
“…A 12−LO isoform has been cloned from cardiac muscle [13] and 12−HETE, the product of 12/15−LO, has been found to be the main LO metabolite in ventricular cardiomyocytes [14]. Our laboratory previously demonstrated the possible involve− ment of 12−HETE in cardiac glucose transport [15,16]. We found that inhibitors of 12−LO led to a disarrangement of actin fibers in isolated rat cardiomyocytes, thus completely disturbing insulin− stimulated GLUT4 translocation and glucose uptake.…”
Section: Introductionmentioning
confidence: 99%
“…This method is also suitable for detecting cell surface GLUT4, notwithstanding that GLUT4 expresses only a single extracellular lysine (at position 50). Accordingly, we (22) and others (11,42) have shown that insulin stimulates the binding of sulfo-NHS-LC-biotin to GLUT4. In the present study, oligomycin, a well-established inducer of GLUT4 and CD36 translocation (32), was used as positive control to validate the suitability of the cell surface biotinylation protocol and also of the other methods to detect surface GLUT4 and CD36.…”
Section: Effects Of Ca 2ϩ -Elevating Stimuli On Glut4 and Cd36 Translmentioning
confidence: 99%